Finlay Donovan is killing it [large type] - Cosimano, Elle (Cosimano, Elle. Finlay Donovan series, 2021)
"Finlay Donovan is killing it . . . except, she's really not. She's a stressed-out single-mom of two and struggling novelist, Finlay's life is in chaos: the new book she promised her literary agent isn't written, her ex-husband fired the nanny without telling her, and this morning she had to send her four-year-old to school with hair duct-taped to her head after an incident with scissors. When Finlay is overheard discussing the plot of her new suspense novel with her agent over lunch, she's mistaken for a contract killer, and inadvertently accepts an offer to dispose of a problem husband in order to make ends meet . . . Soon, Finlay discovers that crime in real life is a lot more difficult than its fictional counterpart, as she becomes tangled in a real-life murder investigation. Fast-paced, deliciously witty, and wholeheartedly authentic in depicting the frustrations and triumphs of motherhood in all its messiness, hilarity, and heartfelt moment,Finlay Donovan Is Killing It is the first in a brilliant new series from YA Edgar Award nominee Elle Cosimano"--